PROTOTYPE APPLICATION AS THE IMPLEMENTATION OF SOFTWARE AS A SERVICE - Citra Noviyasari; Muh Rifki (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2013)
Cloud computing is an internet-based computing process, and Software as a Service is a software in the form of services that are part of Cloud Computing. Cloud computing as a form of market will grow rapidly, can be used as a means of marketing and supply services or goods. This application become a meeting point of the supplier of goods/services with consumer goods / services.